On the analysis of the spot electricity prices - Čurpek, Juraj (2015)
This diploma thesis is devoted to the analysis of the spot electricity prices on the wholesale market. By performing a correlation and regression analysis we search for the relationship between these prices presented on two different power exchanges - NordPool Spot and OMIE, and corresponding temperature in these regions which is important fundamental factor. Our main goal is to calculate the correlation coefficients of the average daily spot electricity prices and the temperature, finding a simple regression model which describes this relationship, explanation of the relationships determined and their comparison with the generally accepted assumptions.